The Irfan Concept in Sufism and Its Relation to Islamic Philosophy - Munandar, Siswoyo Aris; Malikhaturrahmah, Elia (Aqlania, 2021)
This study explores the views of experts regarding the relationship between the science of 'Irfan in Sufism, and philosophy. Talking about Sufism cannot be separated from the science of 'irfan. To reach the level of 'irfan, a Sufi must experience spiritual exercises (riyadhah), then gradually go through various phases, known as maqam (levels) and hals (states), which end with knowing (ma'rifat) to Allah SWT. The level of ma'rifat is a jargon that is generally pursued by Sufis. Then when Sufism meets philosophy, can the two synergize with each other? Sufism talks about the heart, while philosophy talks about reason or reason. This description is the reason for the need for research on the relationship between Sufism (irfan) Islamic philosophy. This research is a literature study using a normative approach. The conclusion of this study is that their studies of the soul in a philosophical approach have made many valuable contributions to the perfection of the study of Sufism in the Islamic world. An understanding of the soul and spirit itself is essential in Sufism. Philosophical studies of the soul and spirit were then widely developed in Sufism.